High permittivity processed SrTiO3 for metamaterials applications at terahertz frequencies. Issue 1 (December 2018) - Dupas, Cyrielle; Guillemet-Fritsch, Sophie; Geffroy, Pierre-Marie; Chartier, Thierry; Baillergeau, Matthieu; Mangeney, Juliette; Roux, Jean-François; Ganne, Jean-Pierre; Marcellin, Simon; Degiron, Aloyse; Akmansoy, Éric
Abstract High permittivity SrTiO3 for the realization of all-dielectric metamaterials operating at terahertz frequencies was fabricated. A comparison of different processing methods demonstrates that Spark Plasma Sintering is the most effective sintering process to yield high density ceramic with high permittivity. We compare this sintering process with two other processes. The fabricated samples are characterized in the low frequency and in the terahertz frequency ranges. Their relative permittivities are compared with that of a reference SrTiO3 single crystal. The permittivity of the sample fabricated by Spark Plasma Sintering is as high as that of the single crystal. The role of the signal-to-noise ratio in the measurements at terahertz frequency is detailed.